Elimination of inter-discharge helium glow discharge cleaning with lithium evaporation in NSTX. (August 2017) - Maingi, R.; Kaita, R.; Scotti, F.; Soukhanovskii, V.A.; ,
Highlights: This paper presents a dedicated scan of the duration of helium flow discharge cleaning (HeGDC) prior to lithium evaporation in NSTX-U. While high performance ELM-free discharges can be obtained with lithium evaporation alone, we find that the use of HeGDC can moderately reduce Dα emission from the far scrape-off layer (SOL), thus reducing the particle source into the SOL. The SOL region near the strike point is unaffected by the use of HeGDC. Thus HeGDC will be a useful tool for experiments that strive for the lower SOL fueling and highest performance discharges. Abstract: Operation in the National Spherical Torus Experiment (NSTX) typically used either periodic boronization and inter-shot helium glow discharge cleaning (HeGDC), or inter-shot lithium evaporation without boronization, and initially with inter-shot HeGDC. To assess the viability of operation without HeGDC, dedicated experiments were conducted in which Li evaporation was used while systematically shrinking the HeGDC between shots from the standard 10 min to zero (10 → 6.5 → 4 → 0). Good shot reproducibility without HeGDC was achieved with lithium evaporations of 100 mg or higher; evaporations of 200–300 mg typically resulted in very low ELM frequency or ELM-free operation, reduced wall fueling, and improved energy confinement. The use of HeGDC before lithium evaporation modestly reduced Dα in the outer scrape-off layer, but not at the strike point. Pedestal electron and ion temperature also improved modestly, suggesting that HeGDC prior to lithium evaporation is a useful tool for experiments that seek to maximize plasma performance.